TRANSFORMING MSME ECONOMIC PRACTICES THROUGH DIGITALIZATION: EVIDENCE FROM SAMOSIR REGENCY, INDONESIA - Shanny Melanova Nainggolan; Harmona Daulay; Martino Martino (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study examines the digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Samosir Regency from the perspective of economic sociology. Using a qualitative approach, the study explores how digitalization reshapes the socio-economic practices of MSMEs through an analysis of social interactions, institutional dynamics, and local community networks. The findings reveal that MSME digitalization is not merely a technological transition or the adoption of digital marketing tools but a broader transformation of socio-economic relations. Digital technologies have reshaped patterns of interaction, created new competitive fields, and shifted economic practices from traditional face-to-face transactions to digitally mediated exchanges. The study further shows that the success of digital transformation is strongly influenced by the embeddedness of economic activities within local social networks. Despite limited digital capabilities, MSME actors have adapted by relying on strong social capital, particularly kinship (marga) networks and local solidarity. Trust-based relationships within traditional communities have become essential resources for technological adaptation. In addition, the local government plays a strategic institutional role by enhancing digital capacity, expanding access to technology, and fostering an ecosystem that supports MSME participation in the digital economy. This study concludes that the digital transformation of MSMEs cannot be adequately explained solely through rational economic approaches emphasizing efficiency or marketing strategies. Instead, an economic sociology perspective demonstrates that social relations, habitus, and local social structures are the primary determinants of successful digital transformation. These findings contribute to the literature by highlighting that technological adoption is fundamentally a socially embedded process rather than merely a technological or economic phenomenon.